2009
DOI: 10.1590/s1413-70542009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Germinação e vigor de sementes de milho recobertas e viabilidade do inóculo durante o armazenamento

Abstract: RESUMOConduziu-se este trabalho com o objetivo de avaliar a qualidade fisiológica das sementes recobertas com diferentes misturas e armazenadas, assim como a sobrevivência das células bacterianas no recobrimento destas. Utilizou-se neste estudo a estirpe H. seropedicae Z67 BR 11175. O recobrimento das sementes de milho 'UENF 506-8' foi realizado com a mistura de calcário, meio de cultura semi-sólido, água e cimentante. As sementes foram acondicionadas durante três meses, em sacos de papel multifoliado e armaze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[21] stated that the water present in the coating is lost faster than that found in the seed itself; for this reason, coated seeds usually have lower WC values than uncoated seeds.…”
Section: Resultsmentioning
confidence: 99%
“…[21] stated that the water present in the coating is lost faster than that found in the seed itself; for this reason, coated seeds usually have lower WC values than uncoated seeds.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the drying process of the coater, at 40°C, was efficient and that the materials have not retained moisture from the adhesive solution. Conceição et al (2009) also found lower water values in coated corn seeds, and claim that the coated seeds have less water content because the water contained in the coating is not absorbed by the seed and it is quickly lost in the process. Therefore, the coated seeds tend to have lower water content, when compared to uncoated seeds.…”
Section: Laboratorymentioning
confidence: 91%